The influence of nutrient management on soil organic carbon storage, crop production, and yield stability varies under different climates. (20th September 2020) - Waqas, Muhammad Ahmed; Li, Yu'e; Smith, Pete; Wang, Xiaohan; Ashraf, Muhammad Nadeem; Noor, Mehmood Ali; Amou, Martial; Shi, Shengwei; Zhu, Yongchang; Li, Jianling; Wan, Yunfan; Qin, Xiaobo; et al.
Abstract: Our understanding on how soil organic carbon (SOC) storage, crop yield, and yield stability are influenced by climate is limited. To critically examine this, the impact of long-term (≥10 years) application of nutrient management practices on SOC storage, crop productivity, and yield stability were evaluated under different climatic conditions in China using a meta-analysis approach. The cropping area of China was divided into four distinct groups based on local climatic conditions (warm dry, DW; warm moist, WM; cool dry, CD; cool moist, CM). Results indicated that the impact of nutrient management practices on SOC storage, crop yield, and yield stability varies under different climatic zone in China. The use of unbalanced mineral fertilizer (UMF), and balanced mineral fertilizer (BMF) led to a loss in SOC storage by 6%, and 11% under CM climatic zone and gains in DW, WM, and CD climates. Organic fertilizers (OF), combined unbalanced mineral and organic fertilizers (UMOF), and combined balanced mineral and organic fertilizers (BMOF) were able to sustain and enhance SOC storage under all climatic conditions. However, the largest increase in SOC storage across all climates was seen for BMOF. Further, corresponding values of crop productivity and yield stability were also highest for BMOF among all the nutrient management treatments. A linear-plateau model indicated that maximal yield responsive SOC stock (Copt ) levels ranged from 33.43 to 45.51 Mg C ha −1 for rice ( Oryza sativa ), maize ( Zea mays ), and wheat ( Triticum aestivum ) production. To enhance and sustain SOC storage, and crop productivity of croplands under different climates, BMOF appears to be the most appropriate nutrient management strategy. Our findings demonstrate that it is essential to optimize nutrient management strategies according to the local climate to protect soil from SOC losses, and for achieving sustainable crop production. Highlights: The impact of nutrient managements on SOC storage, crop yield, and yield stability varies under different climatic zones. Unbalanced mineral, and balanced mineral fertilizer led to a loss in SOC storage by 6%, and 11% under cool moist climate. Combined balanced mineral with organic inputs is crucial for maximal SOC storage and crop yields under different climates. Maximal yield responsive SOC stock levels ranged from 33.43 to 45.51 Mg C ha −1 for rice, maize, and wheat production.